Effect of different stabilisation treatments on preparation and functional properties of rice bran proteins - Shi-Wen LV; Lei-Yu HE; Li-Hui SUN (Czech Journal of Food Sciences, 2018)
The stabilisation treatments of rice bran were performed using microwave heating (100% power, 1-2 min) and dry heating (120°C, 10-20 min), respectively, and then protein was prepared by alkaline extraction (pH 9.5) and acid precipitation (pH 4.5). Stabilisation treatments resulted in a decrease in the protein yield, but an increase in the protein purity. Heat-stabilisation was effective in inhibiting the rancidity of rice bran, and microwave heating was more effective than dry heating. The functional properties of proteins such as the emulsifying properties and oil holding capacity were improved with the stabilised rice bran, while the foaming properties, water holding capacity and nitrogen solubility of protein were slightly impaired. By comparison, dry heating treatment at 120°C for 20 min was effective and suitable for the stabilisation of rice bran for long term storage, as well as improving some functional properties of rice bran proteins. These results could provide basic information for industrial preparation of rice bran protein and its application in various food formulas.